Synergistic QTL interactions between Rf-1 and Rf-3 increase renal damage susceptibility in double congenic rats - Van Dijk, S.J.; Specht, P.A.C.; Lazar, J.; Jacob, H.J.; Provoost, A.P. (Kidney international, 2006)
The FHH (fawn-hooded hypertensive) rat is a model of hypertension-associated chronic kidney damage. Five interacting quantitative trait loci (QTLs), named Rf-1–Rf-5, determine the high renal susceptibility. The aim of the present study was to investigate a possible interaction between Rf-1 and Rf-3. Differences in renal susceptibility between ACI (August × Copenhagen Irish) controls, Rf-1A and Rf-3 single congenics, and Rf-1A+3 double congenic rats were assessed using four different treatments: two-kidney control (2K), 2K plus Nω-nitro-L-arginine methyl ester (L-NAME)-induced hypertension (2K+L-NAME), unilateral nephrectomy (UNX), and UNX plus L-NAME-induced hypertension (UNX+L-NAME). Proteinuria (UPV) and systolic blood pressure (SBP) were assessed after 6, 12, and 18 weeks, while the incidence of glomerulosclerosis (%FGS) was determined at the end of the experiment. In a separate experiment, renal autoregulation was assessed in 13–15-week old 2K rats of all four strains. Compared to ACI rats, small increases in renal susceptibility were found in Rf-1A and Rf-3 single congenics following 2K+L-NAME, UNX, and UNX+L-NAME treatments. However, in the Rf-1A+3 double congenics, a major increase in renal susceptibility was found with all four treatments. Both Rf-1A and Rf-1A+3 congenic rats had an impaired renal autoregulation. In contrast, the Rf-3 had a normal autoregulation, similar to that of the ACI rat. These findings indicate that Rf-1 and Rf-3 alone slightly increase the susceptibility to the development of renal damage. However, a synergistic interaction between these two QTLs markedly enhances renal susceptibility. In contrast to the Rf-1 region, the Rf-3 region does not carry genes influencing renal autoregulation.